Polish Underground Extracts, no. 4 (1985) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Extracts from Polish underground publications compiled and translated into English by the RFE Polish Publication Unit for broadcasting purposes. Introductions to most articles are provided by RFE staff, and items are compiled in issues based mainly on theme and date. When So Ordered / by Edward Kortal[from: Karta, no. 2 (June 1984)]This is an interview with two young men who have recently finished their military service. It was prepared by Edward Kortal for "Karta," a Warsaw underground journal. The men describe their experience in the army during the years of Solidarity and martial law.